One Nation under God: religion in contemporary American society - Kosmin, Barry A. (Harmony Books, 1993)
Presenting the results of the first comprehensive national survey on religious belief, practice, and affiliation in America, this work offers insights into the changing forces that shape our politics and beliefs. 20,000 first printing